Prediction of the Amount of Areca Nut Plantation Production in Riau Province Using the Single Exponential Smoothing - Zukrianto, Zukrianto; Melka Pratama, Melka Pratama (Indonesian Council of Premier Statistical Science, 2025)
Data in this study was obtained from the Riau Provincial Plantation Office. This study aims to forecast areca nut plantation production in Riau Province in 2023. The data used is data obtained from the Riau Provincial Plantation Office in 2011-2022. Betel seeds are generally grown to be used for their seeds, areca nuts that are traded, especially those that have been dried, in a whole (round), split, and there is also by boiling to get the quality of areca nuts to be exported. Betel seeds have been used since hundreds of years ago as one of the mixtures of people eating betel nut in addition to gambier and lime. In addition, areca nuts are also used as industrial raw materials such as fabric dyes and medicines. The separation of areca nuts is carried out by splitting them using a knife or machete, drying them in the sun, then prying and drying them before selling them to collectors. The purpose of this study is to find out the results of predicting the number of areca nut production in Riau Province and find out the results of forecasting the number of areca nut production in Riau Province in 2023. The method used in this study is Single Exponential Smoothing. Based on the results of data processing from 2011 to 2022, the results of this forecast have a MAPE value with α = 0.7 in 2023 of 7.095371%. The results show that the Single Exponential Smoothing method has a good level of accuracy to predict the amount of areca nut production in Riau Province